Fine-Root Decomposition and Nutrient Return in Moso Bamboo (Phyllostachys pubescens J.Houz.) Plantations in Southeast China - Xu, Yaowen; Huang, Runxia; Zhou, Benzhi; Ge, Xiaogai (Frontiers in Plant Science, 2022)
Plant fine-root decomposition is an important pathway for the reentry of nutrients into the soil. Studies have mainly focused on the loss of fine-root mass and the release characteristics of major elements, including, C, N, and P, but there are few reports on trace elements. In this study, in situ decomposition experiments were conducted to study the dynamic characteristics of mass loss and residual rates of 10 mineral elements in two diameter classes (＜2 mm and 2–5 mm) of moso bamboo in the process of fine-root decomposition. The results of the year-long experiment reported herein showed that: 1) fine roots with diameters of less than 2 mm decomposed faster than those with diameters of 2–5 mm; 2) C, N, P, K, Ca, and Mg were released, whereas Fe, Mn, Zn, and Cu were enriched or changed little; 3) decomposition time and root diameter had significant effects on the remaining percentages of C, N, K, Ca, Mg, Mn, Zn, and Cu, and there were interactions among the elements (P < 0.05). The remaining percentages of P and Fe were only affected by decomposition time. This is the first comprehensive report on the variation in 10 elements during the fine-root decomposition of moso bamboo. The study expands our understanding of the release of mineral nutrients during fine-root decomposition, laying a solid theoretical foundation for further research on fine-root decomposition and plant–soil nutrient cycling.